An Exploratory Study of Four Urban Community Libraries in Nampula City, Mozambique: Do They Satisfy Community Informational Needs? - Szabo, Elizabeth Eva; Vieira, Ilidia (Libri, 2017)
This exploratory study describes the characteristics of four independent urban community libraries in Nampula city, located in northern Mozambique, East Africa. In a country where public library services are inadequately equipped to address the educational, informational and cultural needs of its citizens, the emergence of urban community libraries in the city indicates that the population is seeking better alternative sources of information. The study profiles four urban libraries to identify their role in the communities they serve and determine whether they conform to Mostert’s (1998) community library model. A case-study design was used with data collection techniques of structured interviews to collect qualitative data from library directors and librarians, a multiple choice questionnaire to obtain user responses, while further statistical data was obtained from collection, circulation and library user records. Findings indicate these four urban libraries only minimally adhere to Mostert’s model and are instead mimicking existing public and school libraries by catering to predominantly secondary and university level students. As a result, the educational, informational and cultural needs of other key groups in the community, such as the illiterate, neo-literate and disadvantaged, are ignored. This is due to a lack of trained library professionals and restrictive library policies.
Keywords: *tagged; G - Mozambique / Moçambique; G - north / norte; GP - Nampula; L - english / inglês; access to services / acesso a serviços; education / educação

Cidadania e Mudanças na Saúde e Educação em Moçambique: O Cartão de Pontuação Comunitária - Franco, Erika Lopez; Citizen Engagement Programme (CEP) (2017)
Este documento sumariza as aprendizagens feitas ao longo da implementação do Cartão de Pontuação Comunitária (CPC) no quadro do Programa Cidadania e Participação (CEP), o qual terminou em Dezembro de 2017. O CEP foi um programa de responsabilização social que tinha como objectivo final aumentar a influência dos cidadãos na melhoria da qualidade dos serviços de saúde e educação em Moçambique.
Accepted: 2018-04-13T12:59:17Z Publisher: (CEP) Citizen Engagement Programme / Cidadania e Participação
Keywords: G - Mozambique / Moçambique; G - north / norte; GP - Nampula; Health PEA; L - portuguese / português; Northern PEA; access to services / acesso a serviços; citizenship & participation / cidadania e participação; community scorecard (CSC) / cartão de pontuação comunitária (CPC); education / educação; health / saúde

Maternal and Newborn Mortality: Community Opinions on Why Pregnant Women and Newborns Are Dying In Natikiri, Mozambique - Belo, C; Pires, P; Josaphat, J; Siemens, R; Rooke, E; Spence-Gress, C (International Journal of Research, 2017)
Background and objective: maternal and neonatal mortality rates in Mozambique are high, due to insufficient numbers of qualified health workers, lack of equipment and materials, referral system deficiency, difficulties to access health services and gender issues. This study assesses the barriers to health care access, regular attendance at ante natal consultations, institutional delivery and postnatal and neonatal follow-up. This is part of the baseline study for an implementation research project to reduce maternal and neonatal mortality in Natikiri, Nampula, Mozambique. Conclusion: local community members and health professionals were asked to state what they thought would be the best way to intervene. These ideas were then discussed further at a conference with health professionals and government representatives. Six intervention strategies to address identified problems were decided on and will be the basis for the ongoing implementation research project. They were: 1. Expanding family planning especially with adolescents. 2. Community based transport system for pregnant women. 3. Strengthening maternal and child health services by training maternity personnel in obstetrical emergency care and neonatal resuscitation. 4. Providing four quality prenatal visits. 5. Providing quality cesarean deliveries. 6. Supporting the Mozambican Government's campaign against bribery.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; G - north / norte; GP - Nampula; Health PEA; L - english / inglês; access to services / acesso a serviços; gender / género; health - dignified care / saúde - atendimento humanizado / mau atendimento; health - maternal and child / saúde - materno-infantil; health / saúde; ⛔ No DOI found

Maternity care system in Maputo, Mozambique: Plans and practice? - Long, Qian; Madede, Tavares; Parkkali, Saara; Chavane, Leonardo; Sundby, Johanne; Hemminki, Elina (Cogent Medicine, 2017)
Mixed methods were used with various data sources to describe organisation and delivery of maternity care in Maputo city, Mozambique in early 2010s and to compare the plans with the service provision in practice. In the public health sector, maternity care was organised to be area based and hierarchical with a planned referral system. The provision of basic and emergency maternity care was publicly funded, largely dependent of donor funds, and free of charge for users. Even though Maputo City was better resourced than the rest of the country, there was a large lack of health professionals. Women’s choices and self-referrals, even to higher levels of care, were common, which broke the plans of areas responsibility, gate keeping and care by medical needs. Private services for maternity care had emerged for those who were able to pay, leading to dual practices of health professionals and shortage of care providers in the public system at odd hours. Information of maternity care was aggregate and poorly stored. The gap between “planned” services delivery and “practice” in a real-life requires overall health system strengthening to improve efficiency and effectiveness of health services delivery.
Keywords: *indexed; *tagged; G - Maputo City / Cidade de Maputo; G - Mozambique / Moçambique; G - south / sul; GP - Maputo; Health PEA; L - english / inglês; access to services / acesso a serviços; gender / género; health - maternal and child / saúde - materno-infantil; health / saúde

Desafio da articulação entre os cidadãos e os Comités de Qualidade e Humanização dos Cuidados de Saúde como órgãos de representação da comunidade - Dias, José (Centro de Aprendizagem e Capacitação da Sociedade Civil, 2017)
O Ministério da Saúde reconhece os Comités de Qualidade e Humanização dos Cuidados de Saúde nas Unidades Sanitárias como a principal forma de diálogo e ligação entre os serviços de saúde e as comunidades. Os Termos de Referência revistos, afirmam que o Comité de Qualidade e Humanização das Unidades Sanitárias constitui uma equipa de assessoria e coordenação ao processo de implementação da actividades de qualidade e humanização no âmbito da Unidade Sanitária. Destina-se a empreender uma política institucional de resgate de valores humanitários e de garantia de qualidade nos serviços de saúde, em benefício dos utentes e trabalhadores através da gestão participativa. Contudo, o sector de saúde dispõe também da Carta dos Direitos e Deveres do Doente, como instrumento que, no nosso entendimento, define o padrão da prestação de serviços, de comportamento, e concede espaço ao cidadão, individual ou colectivamente, para a exigência directa de serviços de saúde de qualidade. A este último propósito, por exemplo, cabe ressaltar que no quadro do Direito 16 (Direito a apresentar sugestões, queixas e reclamações) é estabelecido que através dos canais disponibilizados pelas Autoridades Sanitárias, os doentes têm direito a apresentar, individual ou colectivamente, petições, sugestões, reclamações ou queixas sobre a organização e o funcionamento dos serviços de saúde; e de ter as suas queixas atendidas prontamente e de maneira equitativa (MISAU, 2011). O que se apreende do exposto é que enquanto os Comités de Qualidade e Humanização funcionam numa lógica essencialmente de Democracia Representativa, a Carta dos Direitos e Deveres do Doente se insere numa abordagem de Democracia Participativa, buscando promover uma cidadania activa do doente/cidadão na sua interacção directa com as unidades sanitárias. O nosso artigo problematiza e discute as dinâmicas de representação e de participação activa do cidadão no processo da prestação de serviços de saúde. A nossa base de discussão é fundamentada em evidências de 15 distritos de actuação do Centro de Aprendizagem e Capacitação da Sociedade Civil (CESC), onde funcionam os Comités de Qualidade e Humanização, por um lado, e se implementa a abordagem de Responsabilização Social, usando ferramentas tais como Cartão de Pontuação Comunitária, por outro.
Keywords: G - Mozambique / Moçambique; Health PEA; L - portuguese / português; access to services / acesso a serviços; citizenship & participation / cidadania e participação; health / saúde